2014
DOI: 10.1016/j.neuroimage.2013.06.062
|View full text |Cite
|
Sign up to set email alerts
|

A wearable multi-channel fNIRS system for brain imaging in freely moving subjects

Abstract: Functional near infrared spectroscopy (fNIRS) is a versatile neuroimaging tool with an increasing acceptance in the neuroimaging community. While often lauded for its portability, most of the fNIRS setups employed in neuroscientific research still impose usage in a laboratory environment. We present a wearable, multi-channel fNIRS imaging system for functional brain imaging in unrestrained settings. The system operates without optical fiber bundles, using eight dual wavelength light emitting diodes and eight e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
303
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(325 citation statements)
references
References 69 publications
3
303
0
Order By: Relevance
“…Given the need to bring functional imaging instruments outside the lab and given recent technological improvements, portable and wearable electroencephalography (EEG) and functional near infrared spectroscopy (fNIRS) systems have been developed [6][7][8][9][10][11] . One of the major advantages of fNIRS over EEG is its higher spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the need to bring functional imaging instruments outside the lab and given recent technological improvements, portable and wearable electroencephalography (EEG) and functional near infrared spectroscopy (fNIRS) systems have been developed [6][7][8][9][10][11] . One of the major advantages of fNIRS over EEG is its higher spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The first fiberless systems were equipped only with a small number of channels (e.g., single channel 15 and 2 channels 16 ) limiting the investigation to small areas. More recently, multichannel wireless and wearable fNIRS devices have been developed 6,7,[17][18][19][20] giving the possibility to monitor larger portions of the head on freely moving participants.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the block-averaged hemodynamic responses were calculated. A typical cerebral activation is characterized by a significant increase in HbO concentration or a significant decrease in HbR concentration with respect to the baseline after the activation onset [38]. The spatial distribution maps of the groupaveraged hemodynamic responses were calculated based on the maximum values of the group-averaged hemodynamic responses from 5 seconds after the stimulation onset until the end of the stimulation.…”
Section: Fnirs Recording and Data Analysismentioning
confidence: 99%
“…Moreover, the rate of increase in the HbO concentration was greater than the rate of decrease in the HbR concentration. This may be due to a relatively higher signal-to-noise ratio for HbO, which can improve its robustness to cross-talk [38]. For a given stimulus, the changes in the hemodynamic response are produced by a series of complex processes, including the neuronal activity responding to the stimulus, the neurovascular coupling between the neuronal and the hemodynamic responses, and the characteristics of the hemodynamic response itself [49].…”
Section: Hemodynamic Response To Hemifield Stimulationmentioning
confidence: 99%
“…Several studies have shown that these wireless NIRS devices produce nearly artifact free and reproducible data. 70 fNIRS can measure changes in O 2 saturation both centrally on the level of the cortex and peripherally at the level of muscles. Further, it is portable and not easily susceptible to movement artifacts.…”
Section: Electroencephalography (Eeg)mentioning
confidence: 99%